Pityriasis lichenoides chronica following SARS-CoV-2 infection: A case report and brief report of the literature - Yusuf Can Edek; Fatma Sena Gürevin; Nilsel İlter (Turkderm Turkish Archives of Dermatology and Venereology)
Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) is a newly identified type of coronavirus that causes coronavirus disease-2019 (COVID-19) and has been associated with numerous skin manifestations. Although COVID-19 primarily affects the respiratory system, it can also involve many systems, such as the cardiovascular, gastrointestinal, and urogenital systems, in the course of the disease. Skin findings can be observed frequently in the course of the disease. Pityriasis lichenoides (PL) is an inflammatory skin disease that includes pityriasis lichenoides et varioliformis acuta (PLEVA) and pityriasis lichenoides chronica (PLC). PLEVA is characterized by erythematous papules, vesicles, ulcers, and hemorrhagic crust formation, which can be observed in the lesions over time. PLC is characterized by red-brown papules and plaques with mica-like scales. Extrinsic antigens such as drugs, infections, and vaccines can trigger the immune system and cause disease development. In addition, immune complex-mediated hypersensitivity reactions due to etiological factors and clonal T-lymphocyte proliferation are also involved in the etiopathogenesis of the disease. Viral infectious agents in etiology include Epstein-Barr virus, cytomegalovirus, varicella-zoster virus, and parvovirus-B19. SARS-CoV-2 may play an important role in the etiopathogenesis of dermatological diseases. Although the apparent relationship between PL and SARS-CoV-2 is not fully understood, cases of SARS-CoV-2-triggered PL have been reported. This case report presents a rare case of PLC triggered by SARS-CoV-2 infection.